INDONESIAN EFL STUDENTS’ ATTITUDE TOWARD FACE BOOK FOR ENGLISH LEARNING - Ani Susanti (Universitas Negeri Padang, 2013)
The amount of students at higher education using face book is running at a phenomenal level, but less has been reported in the context of EFL in Indonesia on how students consider face book as English learning tool. This paper reports the survey involving 374 undergraduate students at English department of Ahmad Dahlan University Yogyakarta. The study was designed to explore how Indonesian EFL students view the potential of face book as a tool to support their English learning; and how face book has influenced their foreign language acquisition. The instrument of this survey was a questionnaire uses five-level likert scale and open question. The result of the survey indicates that the students believe in the language learning opportunities provided by face book. Most of students agree that face book offers promises to facilitate them learn English skills and to improve their motivation and confidence to communicate using English. However, this belief does not portray the students’ practice of using face book for English learning. A number of students never uses face book for English learning purpose. Given the huge number of the students using face book, EFL teachers in Indonesia are challenged to find ways to integrate face book to achieve the success of TEFL.